2022
DOI: 10.1021/acs.macromol.1c01808
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Promotes Hydrogen Bond Network Formation and Grotthuss Proton Hopping in Ion-Conducting Block Copolymers

Abstract: Proton-conducting polymer membranes frequently contain nanoscale structural and ion-conducting phases. In addition to enhancing the mechanical properties, this mesoscale structure often leads to a significant increase in ion dynamics; however, the molecular underpinnings behind this phenomenon are not well understood. Here, a model proton-conducting polymeric ionic liquid (PIL) block copolymer is shown to have conductivity up to an order of magnitude higher than an analogous homopolymer. Variable temperature 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…While the morphological features reported in the above experiments arise from the crystallization of one or more domains, a more straightforward approach to achieving morphological diversity in polyILs is to transition toward block copolymer ILs. Indeed, depending on the composition and the interaction between the different blocks, block copolymer polyILs have been demonstrated to exhibit a variety of morphologies. Such self-assembled equilibrium structures present a richer variety of opportunities for retarding the motion of the polymerized ionic backbone while confining the motion of the counterion within the conducting domain. Moreover, by combining a conductive block with a mechanically strong block, such copolymers provide an opportunity to overcome the trade-off between conductivity and mechanical strength. ,, However, despite the emerging interest in such multicomponent polymeric electrolyte systems, there is very little known about the impact of self-assembly and morphology on the dynamical ionic correlations in single ion block copolymeric conductors such as polyILs. , …”
mentioning
confidence: 99%
“…While the morphological features reported in the above experiments arise from the crystallization of one or more domains, a more straightforward approach to achieving morphological diversity in polyILs is to transition toward block copolymer ILs. Indeed, depending on the composition and the interaction between the different blocks, block copolymer polyILs have been demonstrated to exhibit a variety of morphologies. Such self-assembled equilibrium structures present a richer variety of opportunities for retarding the motion of the polymerized ionic backbone while confining the motion of the counterion within the conducting domain. Moreover, by combining a conductive block with a mechanically strong block, such copolymers provide an opportunity to overcome the trade-off between conductivity and mechanical strength. ,, However, despite the emerging interest in such multicomponent polymeric electrolyte systems, there is very little known about the impact of self-assembly and morphology on the dynamical ionic correlations in single ion block copolymeric conductors such as polyILs. , …”
mentioning
confidence: 99%
“…7,12,51 It has been recently demonstrated that confinement in an anhydrous nanostructured polymeric ionic liquid (PIL) block copolymer reduces PIL segmental mobility and enhances the connectivity of the hydrogen-bonding network, which results in a significant boost in proton dynamics. 52…”
Section: Resultsmentioning
confidence: 99%
“…7,12,51 It has been recently demonstrated that confinement in an anhydrous nanostructured polymeric ionic liquid (PIL) block copolymer reduces PIL segmental mobility and enhances the connectivity of the hydrogen-bonding network, which results in a significant boost in proton dynamics. 52 Moreover, we have applied similar calculations for confined atactic polystyrene (PS) 53 between charged MoS 2 layers as a polymer system that is not able to form hydrogen bonds. The thermal conductivity of pure PS containing 300 chains with the density of 1.01 g cm À3 at 350 K and 1 atm amounts to (0.173 AE 0.008) W m À1 K À1 , which agrees with the experimental one 54 and MD simulation results at the same temperature and pressure.…”
Section: Soft Matter Papermentioning
confidence: 99%
“…Characterization. 1 H NMR was measured using a Bruker 400 MHz spectrometer in CDCl 3 . GPC analysis was conducted using an Agilent 1260 system with polystyrene as standard and THF as eluent.…”
Section: Formation Of P3bt-b-p3hs Thin Films Via Meniscus-assisted So...mentioning
confidence: 99%
“…Block copolymers (BCPs) are widely recognized as an important class of nanomaterials as they are thermodynamically driven to self-assemble into well-ordered, periodic nanostructures. In stark contrast to the broadly studied coil–coil BCPs, the study on conjugated rod–rod BCPs is surprisingly limited due largely to their rigid chain characteristic. , As rod-like polymers (e.g., polypeptides, DNA, π-conjugated polymers) are capable of crystallization, , two phase behaviors (i.e., microphase separation and crystallization) greatly compete with one another in conjugated rod–rod BCPs. As a result, it remains challenging to thoroughly understand the phase behavior and associated phase transition in conjugated rod–rod BCPs both experimentally and theoretically. …”
Section: Introductionmentioning
confidence: 99%